PERAN KEPUASAN KERJA DALAM MEMEDIASI PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (STUDI KASUS DI PT. PLN UNIT PELAKSANAAN PELAYANAN PELANGGAN TERNATE) - Ahmad, Siti Humaira T.; Arilaha, Muhammad Asril; Soleman, Marwan Man (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2023)
bjectives: The research objectives are to determine: (1) To determine whether there is an influence of organizational culture and work environment on job satisfaction; (2) To find out whether there is an effect of job satisfaction and organizational culture on the performance of employees; (3) To find out whether there is an influence of the work environment on the performance satisfaction; (4) To find out whether there is an influence of organizational culture on performance with job satisfaction through intervening variables on employees; (5) To find out whether there is an influence of the work environment on employee performance with job satisfaction through intervening variables on employees of PT. PLN (Persero) Ternate. The total number of 52 respondents in the research samples.Methodology: The data obtained is then processed using the SmartPLS version 3.0 analysis tool. This analysis includes descriptive statistical tests and inferential statistical analysis tests. Findings: Because the statistical t value exceeds the t table and the p value is less than alpha 0.05, the first, second, third, fourth, fifth, sixth, and seventh hypotheses are accepted. Conclusion: The conclusions in this research are: (1) organizational culture and work environment Â has a significant and positive effect on job satisfaction;Â (2) job satisfaction has a significant and positive effect on employee performance; (3) organizational culture has a significant positive effect on employee performance; (4) the work environment does not have a significant positive effect on employee performance; (5) there is an indirect effect of organizational culture on employee performance through job satisfaction as a significant positive intervening variable; (6) there is an indirect effect of the work environment on employee performance through job satisfaction as a significant positive intervening variable.